Health Insurance for the Informal Sector in Africa : Design Features, Risk Protection, and Resource Mobilization - Arhin-Tenkorang, Dyna (World Bank, Washington, DC, 2013)
Studies and literature reviews of health insurance schemes targeting rural or informal sector populations in developing countries (often called "community insurance schemes") frequently conclude that schemes have design weaknesses, yet do not explore in detail the effect of design features on performance. This paper presents a conceptualization of how performance in the areas of risk protection and resource mobilization is determined by the interaction of design features with institutional and technical factors. Design features refer to scheme specifications (e.g., required contribution) and to operating modalities (e.g., procedures for enrolment or obtaining benefits. Performance, with respect to risk protection and resource mobilization, of several potential "high population schemes" for the informal sector in Africa, is assessed. The outcome suggests that the design of community health insurance schemes may be improved by: (1) design specifications that utilize data on willingness to pay (WTP) of the target population and projected health care costs; and (2) incorporating modalities of operations that facilitate cost-effective exchange between a formal organization and individuals acting in an informal environment.